Raw microalgae based biochar application in agriculture / Irfan Zulkarnain Roszri - Roszri, Irfan Zulkarnain (2023)
This report explores the characteristics, ecological significance, and potential applications of microalgae belonging to the Chlorophyta division. Chlorophyta, commonly known as green algae, are photosynthetic organisms found in diverse aquatic environments. They play a crucial role in carbon sequestration, biofuel production, wastewater treatment, and as a nutritional resource. This study focuses on analyzing different surface media for microalgae growth and their potential impact on plant development.